Air passenger attitudes towards pilotless aircraft. (December 2021) - Bennett, Roger; Vijaygopal, Rohini
Abstract: This paper presents the results of an investigation into attitudes towards and willingness to fly in pilotless aircraft (PAs) among a sample of 711 UK people known to fly at least occasionally. A problem with past studies in the area is that attitudes have only been measured explicitly, using questionnaire items drawn from literature in the field. Also, distinctions between attitude strength and attitude structure have not been considered. The present investigation employed an implicit measure of attitudes and examined attitudes via (i) a structural topic modelling procedure (in order to measure the structure of attitudes within the sample) and (ii) an Implicit Association Test (to evaluate attitude strength). Outcomes to the Implicit Association Test contributed significantly and substantially to the explanation of the sample members' degrees of willingness to fly in PAs. These are important matters considering the need for airlines, government agencies and aircraft manufacturers to induce public acceptance of PAs. Determinants of attitudes were posited to include self-image congruence, fear of flying, general anxiety syndrome, interest in new technologies, age, gender, and exposure to information about pilotless aircraft. A model containing these variables was assembled and estimated, the results providing a good fit (R 2  = 0.58) with data obtained from the sample. Three primary components of attitude emerged from the investigation: risk, excitement and innovation. Four variables exerted the greatest effects on attitude structure, namely self-congruence, interest in new technologies, prior knowledge of PAs, and the age of the participant. Fear of flying and generalised anxiety impacted on the risk element of attitude structure, but not on excitement, innovation or attitude strength. Neither the fear of flying variable nor generalised anxiety had significant influences on attitude strength, although they did have significantly negative effects on willingness to fly in a pilotless airplane. Thirty-one per cent of the sample members disagreed or strongly disagreed with a question (five-point scale) asking whether a person was willing to fly in a pilotless aircraft. The results of the study have important implications for public information campaigns initiated by state agencies and for the marketing activities and promotional messages of airlines that will need to seek public acceptance of pilotless aircraft. Highlights: Examines attitudes towards pilotless aircraft and assesses people's willingness to fly in them. Distinguishes between attitude structure and attitude strength. Uses a structural topic model to measure attitude structure and an Implicit Association Test to evaluate attitude strength. Employs regression analyses to identify key determinants of attitudes and willingness to fly in pilotless aircraft. Offers suggestions for public information and commercial marketing campaigns promoting pilotless aircraft.